2007
DOI: 10.1021/ja068027r
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density of Divalent Metal Cations Determines RNA Stability

Abstract: RNA molecules are exquisitely sensitive to the properties of counterions. The folding equilibrium of the Tetrahymena ribozyme is measured by non-denaturing gel electrophoresis in the presence of divalent group IIA metal cations. The stability of the folded ribozyme increases with the charge density (ζ) of the cation. Similar scaling is found when the free energy of the RNA folded in small and large metal cations is measured by urea denaturation. Brownian dynamics simulations of a polyelectrolyte show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(230 citation statements)
references
References 68 publications
9
216
4
Order By: Relevance
“…Moreover, recent studies have shown valence, size, and shape of counterions profoundly influence RNA folding. [147][148][149][150][151] Despite the complexity, it is possible to devise physics-based models that capture the essential aspects of RNA folding and dynamics. In order to provide a framework for understanding and anticipating the outcomes of increasingly sophisticated experiments involving RNA we have developed two classes of models.…”
Section: Rna Foldingmentioning
confidence: 99%
“…Moreover, recent studies have shown valence, size, and shape of counterions profoundly influence RNA folding. [147][148][149][150][151] Despite the complexity, it is possible to devise physics-based models that capture the essential aspects of RNA folding and dynamics. In order to provide a framework for understanding and anticipating the outcomes of increasingly sophisticated experiments involving RNA we have developed two classes of models.…”
Section: Rna Foldingmentioning
confidence: 99%
“…In the past decades, extensive experiments have been performed to investigate how metal ions promote RNA tertiary structural folding and stabilize tertiary structures; see Table 3 [16,19,32,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. These experiments have revealed several important roles of metal ions, especially Mg 2+ , in tertiary structural folding as shown below:…”
Section: Stabilization Of Tertiary Structuresmentioning
confidence: 99%
“…Native gel electrophoresis experiments [67] showed that higher [Mg 2+ ] and metal ions of higher charge density (charge/volume) would significantly stabilize the non-specific collapsed intermediates. The stabilization of the nonspecific collapsed state slows down the (productive) folding to the final native state which requires the formation and stabilization of specific native contacts [49,67]. In addition, a recent experiment showed that, depending on the ionic condition of the solution, the kinetic partitioning of the folding flux can be dependent on the initial conformational ensemble [68].…”
Section: Tetrahymenamentioning
confidence: 99%
“…As mentioned above, solution conditions (especially monovalent and divalent cation concentration) significantly alter the three-dimensional (3D) conformation of RNA (Heilman-Miller et al 2001a;Takamoto et al 2002Takamoto et al , 2004Koculi et al 2007). Chemical and enzymatic probes are often used to study the effects of solution conditions on the structure of RNA (Vary and Vournakis 1984b;Celander and Cech 1991;Mathews et al 1997;Uchida et al 2003;Takamoto et al 2004).…”
Section: Applications Example Use Casesmentioning
confidence: 99%